Ask your own question, for FREE!
Mathematics
OpenStudy (anonymous):

Let f(x) = –4x + 7 and g(x) = 10x – 6, find f(g(x)).

jimthompson5910 (jim_thompson5910):

The idea is to start with f(x) = –4x + 7 and replace each 'x' with 'g(x)' So f(x) = –4x + 7 becomes f(g(x)) = –4(g(x)) + 7 Then replace the "g(x)" on the right side with "10x-6" to get f(g(x)) = –4(10x-6) + 7 From here, simplify.

Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!
Latest Questions
Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!